Editorial statement: Why do we need a European Journal of Government and Economics? - Diego Varela; Giacomo Benedetto; Jose Manuel Sanchez-Santos (European Journal of Government and Economics (EJGE), 2012)
In this editorial statement we explain the reasons for the creation of the European Journal of Government and Economics. We argue that there is a general shortage of academic journals. Although the new journal we are starting will not solve or significantly reduce this problem, it will represent a marginal step in the right direction. We also explain our views regarding some important aspects of the journal's policy, such as indexing and open access.
Keywords: 330